Diffusion tensor imaging tractography reveals altered fornix in all diagnostic subtypes of multiple sclerosis. Issue 1 (19th December 2019) - Valdés Cabrera, Diana; Stobbe, Robert; Smyth, Penelope; Giuliani, Fabrizio; Emery, Derek; Beaulieu, Christian
Abstract: Introduction: Diffusion tensor imaging (DTI) has shown abnormalities of the fornix and other limbic white matter tracts in multiple sclerosis (MS), mainly focusing on relapsing‐remitting MS. Methods: The goal here was to evaluate the fornix, cingulum, and uncinate fasciculus with DTI tractography at 1.7 mm isotropic resolution in three MS subgroups (11 relapsing‐remitting (RRMS), nine secondary progressive (SPMS), eight primary progressive (PPMS)) versus 11 controls, and assess correlations with cognitive and clinical scores. Results: The MS group overall showed extensive diffusion abnormalities of the fornix with less volume, lower fractional anisotropy (FA), and higher mean and radial diffusivities, which were similarly affected in all three MS subgroups. The uncinate fasciculus had lower FA only in the secondary progressive subgroup, and the cingulum had no DTI differences in any MS subgroup. The FA and/or volumes of these tracts correlated negatively with larger total lesion volume. The only DTI‐cognitive correlation was lower right cingulum FA and greater depression over the entire MS cohort. Conclusions: Diffusion tractography identified abnormalities in the fornix that appears to be affected early and consistently across all three primary MS phenotypes of RRMS, SPMS, and PPMS regardless of Expanded Disability Status Scale, time since diagnosis, or cognitive scores. Abstract : Multiple sclerosis (MS) often results in cognitive dysfunction, fatigue, and depression, which may have a microstructural basis in limbic white matter tract degradation. High‐resolution diffusion tensor imaging (DTI) tractography at 4.7T assessed the fornix, cingulum, and uncinate fasciculus tracts and their links to clinical/cognitive scores in three MS diagnostic subgroups. The entire MS cohort showed diffusion abnormalities of the fornix with less volume, lower fractional anisotropy (FA), and higher mean and radial diffusivities, which were similarly affected in all three MS subgroups, and FA and/or volumes of these tracts correlated negatively with larger total lesion volume regardless of Expanded Disability Status Scale, time since diagnosis, or cognitive scores.